Impact of K doping on room-temperature temperature coefficient of resistivity of La0.7(Ag0.3-xKx)MnO3 (0.160 ≤ x ≤ 0.180) polycrystalline ceramics. Issue 17 (1st September 2021) - Jin, Shuaizhao; Zhang, Shuai; Yu, Xiaohan; Guan, Xiaoli; Li, Hongjiang; Chu, Kaili; Pu, Xingrui; Gu, Xin; Liu, Xiang
Abstract: Herein, La0.7 (Ag0.3- x K x )MnO3 (LAKMO, x  = 0.160, 0.165, 0.170, 0.175 and 0.180) polycrystalline ceramics are prepared by the sol-gel method and the influence of K content on the structure of LAKMO ceramics is investigated using X-ray powder diffraction (XRD), field-emission scanning electron microscope (FESEM), Fourier transform infrared (FTIR) and Raman spectroscopy, demonstrating that variations in K content cause significant structural changes. For instance, K doping led to the distortion of MnO6 octahedron and grain growth. Moreover, the energy dispersive spectrometer (EDS), elemental mapping and X-ray photoemission spectroscopy (XPS) confirmed the uniform distribution of constituent elements on the surface. The increase in K-doping ratio resulted in the distortion of MnO6 octahedron, weakening grain boundaries scattering and enhancing the double exchange effect. Consequently, the electrical transport properties of LAKMO ceramics were improved with the increase of K doping, especially the decrease in resistivity and increase in temperature coefficient of resistivity ( TCR ) values. At x  = 0.175, the peak TCR value was found to be 11.15% K −1 at room temperature ( T k  = 292.22 K). These results indicated that the K-doped LAKMO ceramics are promising candidates for uncooled infrared bolometers.